1968
DOI: 10.3758/bf03206311
|View full text |Cite
|
Sign up to set email alerts
|

Visual backward masking in retardates and normals

Abstract: DOWhen the onset of a visual stimulus (S, ) follows immediately or shortly after the offset of another visual stimulus (SI ) at the same point in space, and when S, (the masking stimulus) has appropriate contours, duration, and illumination relative to SI, then SI will be inhibited. The blanking of SI by S, is one instance of a phenomenon labelled "backward masking" (see Raab, 1963, for a review). That perception of SI can be voided by an ensuing stimulus indicates that SI requires a period of time after offse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1
1

Year Published

1972
1972
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 8 publications
3
13
1
1
Order By: Relevance
“…First, the mean individually determined SOA for e^ch of the five groups in the study was comparable. The nonretarded adult groups did not differ fi-om the mildly retarded and child groups, a finding that is inconsistent with some earlier masking studies which have indicated that nonretarded adults are better (more accurate at shorter SOAs) than mentally retarded and equal-MA matched subjects in their ability to identify a masked stimulus (Mosley 1980;Saccuzzo et al 1979;Spitz & Thor 1968;Welsandt & Meyer 1974). Second, the present findings revealed that the experimental SOA remained stable across the 120 experimental trials for all subjects in each of the groups.…”
Section: Durabilitycontrasting
confidence: 81%
“…First, the mean individually determined SOA for e^ch of the five groups in the study was comparable. The nonretarded adult groups did not differ fi-om the mildly retarded and child groups, a finding that is inconsistent with some earlier masking studies which have indicated that nonretarded adults are better (more accurate at shorter SOAs) than mentally retarded and equal-MA matched subjects in their ability to identify a masked stimulus (Mosley 1980;Saccuzzo et al 1979;Spitz & Thor 1968;Welsandt & Meyer 1974). Second, the present findings revealed that the experimental SOA remained stable across the 120 experimental trials for all subjects in each of the groups.…”
Section: Durabilitycontrasting
confidence: 81%
“…Often we find a transfer of the same methods and observation procedures from a study on normal subjects to a study with mentally retarded children or adults, although a qualitative difference in their performances has not been demonstrated. It is well established that mentally retarded subjects tend to show a quantitatively lower ability in the assumption and elaboration of information [Spitz and Thor, 1968;Olson, 19711, but many researchers suggest the existence also of qualitative differences [Abercrombie, 1964;Crosby, 1972;Miranda and Fantz, 1973;Morozas and May, 19851. An early and specific diagnosis of perceptual and cognitive abilities of DS persons may contribute to our knowledge of the evolution of these aspects of their aging. In a previous study [Saviolo-Negrin and lkevisan, 19881, visual-perceptual abilities, which present a particularly significant decline in the first stage of Alzheimer disease [Wisniewski et al, 19851, were tested in 52 DS adults using the Development Test of Visual Perception (DTVP) of Frostig et al [1963].…”
Section: Introductionmentioning
confidence: 99%
“…Apparatus and procedure.-The target stimuli were the letters "D," "O," and "S," and the mask a crosshatched rectangular box similar to that used by Spitz and Thor (1965). For the simultaneous condition, the mask and letters were placed upon the same card.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, previous developmental studies of visual masking have either reported monotonic decreases in masking strength as the interval between the onset of the mask and target increases (Spitz & Thor 1965) or have used measures which tend to assume such a relation (e.g., Pollack 1965). Among adults, however, the relation between stimulus onset asynchrony (SOA) and masking effectiveness is frequently curvilinear rather than monotonic (Weisstein 1968).…”
mentioning
confidence: 99%